Saraba Itik: Representasi Simbol Dalam Identitas Kultural Masyarakat Kabupaten Hulu Sungai Utara - Maulidan, Zia; Hakim, Arif Rahman (Huma: Jurnal Sosiologi, 2024)
The cultural identity symbols that appear in Hulu Sungai Utara Regency have a uniqueness that is different from other districts. This research aims to find out in what ways the duck symbol is used by the people of Hulu Sungai Utara Regency and the meanings of the duck symbol. This research uses a qualitative method with an interpretative approach. Data collection techniques used observation, interviews, and documentation. This research is located in Hulu Sungai Utara Regency. The data analysis technique used the Miles and Huberman interactive model. The results of this study indicate that the cultural identity symbols of the Hulu Sungai Utara Regency community are seen in five aspects: 1) The aspect of duck farming as one of the livelihoods of the people in Hulu Sungai Utara Regency; 2) The culinary aspect has baked boneless ducks; 3) The souvenir aspect has sugar cubes in the shape of ducks; 4) The ornament aspect is used as a city icon and is displayed in the welcome gate, as well as displayed in decorative lights; 5) The cultural arts aspect is displayed in the lyrics of a song entitled Amuntai Banuaku and in the sarigading ikat weaving motif. This duck statue is a medium for tourists from inside and outside the Hulu Sungai Utara Regency area. Judging from its embodiment, the duck statue has a meaning as a sign of the welfare of farmers in Hulu Sungai Utara Regency. With the presence of these symbols, it is recognized by the wider community culturally through the duck symbol. It is hoped that the Hulu Sungai Utara Regency government can make a book about the duck symbol so that people can find out what meaning is contained in the Duck symbol itself.